Optimalisasi Re-branding, Digital Marketing, Management Auditing menjadi Kelurahan Wirausaha Berkelanjutan - Yonsa, Rahmania Risky Putri; Prameswari, Fareh; Setyowati, Diah Kin Kin; Darmawan, Bagus; Rizkia, Alvin Rizal Hafiz; Ananda, Maulana Wahyu; Nikmah, Alfiyatun; Matulessy, Zaschia Flanivolya; Merisa, Fara Elsa; Rachmania, Arikah (Journal Of Human And Education (JAHE), 2024)
MSMEs (Small, Micro and Medium Enterprises) face challenges in maintaining their existence and increasing the competitiveness of their businesses in attracting consumers, including pastry businesses in Dukuh Menanggal Village. This research aims to explore rebranding, digital marketing and management auditing strategies that can be applied by MSME players in Dukuh Menanggal Village to increase the competitiveness and productivity of their businesses. The implementation of this community service activity is implemented in the form of education through program seminars, training and program execution accompanied by monitoring of pastry MSME players in Dukuh Menanggal Village. The results of this community service activity show an increase in brand awareness and sales through digital platforms as well as improved financial records in the internal management of MSMEs. So that this service program has succeeded in having a positive impact in supporting the growth of pastry MSMEs in Dukuh Menanggal Village.